2018
DOI: 10.1111/dth.12691
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood toll-like receptor 4 correlates response to candida immunotherapy of warts

Abstract: Human papilloma virus infection may be self-limiting; however, some cases may spread. There are no factors predicting the prognosis of such infections. The present study aimed to evaluate the significance of TLR4 expression in predicting the response of warts to candida immunotherapy. A total of 60 patients with different types of warts were included in the present study. A total volume of 2 ml venous blood was collected and real-time polymerase chain reaction was used to determine expression of TLR4. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
(32 reference statements)
2
7
0
Order By: Relevance
“…Our study showed absence of a significant correlation between age, sex, and the response to treatment in both group I and II, and this is consistent with Mohamed et al and Raghukumar et al In contrast, El‐Taweel et al and Sabry et al reported better response of younger patients for warts treatment as younger patients are more capable of mounting effective immune responses.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed absence of a significant correlation between age, sex, and the response to treatment in both group I and II, and this is consistent with Mohamed et al and Raghukumar et al In contrast, El‐Taweel et al and Sabry et al reported better response of younger patients for warts treatment as younger patients are more capable of mounting effective immune responses.…”
Section: Discussionsupporting
confidence: 91%
“…This denotes that younger patients are more capable of mounting an effective immune responses. Sabry, Hamed, Salem, Marei, and El Sebaey () reported better response of younger patients to the intralesional injection of candida antigens for warts treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 54 studies of 3,446 enrolled patients was deemed finally eligible [Table 2]. Overall, 13 studies with 747 patients in the MMR group [10][11][12][13][14][15][16][17][18][19][20][21][22] ; 12 studies with 436 patients in the Candida group [23][24][25][26][27][28][29][30][31][32][33][34] ; nine studies with 311 patients in the Vitamin D group 25,[35][36][37][38][39][40][41][42] ; six studies with 235 patients in the PPD group 38,[43][44][45][46][47] ; six studies with 197 patients in the interferon-α group [48][49][50][51][52][53] ; four studies with 127 patients in the Mw group [54]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The overall complete response rate was 60.6% (95% confidence interval: 54.8-66.5%) among 53 studies with 2,548 patients [Figure 2a]. The complete response ratio of the Mw group was 73.1% (95% confidence interval: 55.6-90.6%) in four studies, [54][55][56][57]63 the Candida group was 62.6% (95% confidence interval: 53.3-71.9%) in 11 studies, 23,24,[26][27][28][29][30][31][32][33][34] MMR group was 63.2% (95% confidence interval: 53.1-73.4%) in 13 studies, [10][11][12][13][14][15][16][17][18][19][20][21][22] PPD group was 62.7% (95% confidence interval: 42.4-83.0%) in six studies, 38,[43][44][45][46][47] Vitamin D group was 54.2% (95% confidence interval: 32.7-76.0%) in eight studies, [35][36][37][38][39][40][41][42] interferon-α group was 51.9% (95% confidence interval: 27.0-76.9%) in six studies, [48]…”
Section: Treatment Response Of Injected and Nearby Lesionsmentioning
confidence: 99%